Development of a High-Throughput Cul3-Keap1 Time-Resolved Fluorescence Resonance Energy Transfer (TR-FRET) Assay for Identifying Nrf2 Activators. (February 2019) - Poore, Derek D.; Hofmann, Glenn; Wolfe, Lawrence A.; Qi, Hongwei; Jiang, Ming; Fischer, Michael; Wu, Zining; Sweitzer, Thomas D.; Chakravorty, Subhas; Donovan, Brian; Li, Hu
Nrf2, a master regulator of the phase II gene response to stress, is kept at low concentrations in the cell through binding to Keap1, an adaptor protein for the Cul3 ubiquitin ligase complex. To identify Nrf2 activators, two separate time-resolved fluorescence resonance energy transfer (TR-FRET) assays were developed to monitor the binding of Nrf2-Keap1 and Cul3-Keap1, respectively. The triterpenoid, 1-[2-cyano-3-, 12-dioxooleana-1, 9(11)-dien-28-oyl] imidazole (CDDO-Im) and its analogs, exhibited approximately 100-fold better potency in the Cul3-Keap1 assay than in the Nrf2-Keap1 assay, and this difference was more profound at 37 °C than at room temperature in the Nrf2-Keap1 assay, but this phenomenon was not observed in the Cul3-Keap1 assay. A full diversity screen of approximately 2, 200, 000 GSK compounds was run with the Cul3-Keap1 TR-FRET assay and multiple chemical series were identified and characterized.